Early Pregnancy Serum Metabolite Profiles Associated with Hypertensive Disorders of Pregnancy in African American Women: A Pilot Study - Erin P. Ferranti; Jennifer K. Frediani; Rebecca Mitchell; Jolyn Fernandes; Shuzhao Li; Dean P. Jones; Elizabeth Corwin; Anne L. Dunlop (Journal of Pregnancy)
Hypertensive disorders of pregnancy (HDP) are the most common cardiometabolic complications of pregnancy, affecting nearly 10% of US pregnancies and contributing substantially to maternal and infant morbidity and mortality. In the US, women of African American race are at increased risk for HDP. Early biomarkers that reliably identify women at risk for HDP remain elusive, yet are essential for the early identification and targeting of interventions to improve maternal and infant outcomes. We employed high-resolution metabolomics (HRM) to identify metabolites and metabolic pathways that were altered in early (8-14 weeks) gestation serum samples of pregnant African American women who developed HDP after 20 weeks’ gestation (n=20)—either preeclampsia (PE; n=11) or gestational hypertension (gHTN; n=9)—compared to those who delivered full term without complications (n=80). We found four metabolic pathways that were significantly (p<0.05) altered in women who developed PE and five pathways that were significantly (p<0.05) altered in women who developed gHTN compared to women who delivered full term without complications. We also found that four specific metabolites (p<0.05) were distinctly upregulated (retinoate, kynurenine) or downregulated (SN-glycero-3-phosphocholine, 2′4′-dihydroxyacetophenone) in women who developed PE compared to gHTN. These findings support that there are systemic metabolic disruptions that are detectable in early pregnancy (8-14 weeks of gestation) among pregnant African American women who develop PE and gHTN. Furthermore, the early pregnancy metabolic disruptions associated with PE and gHTN are distinct, implying they are unique entities rather than conditions along a spectrum of the same disease process despite the common clinical feature of high blood pressure.